2021
DOI: 10.1371/journal.pone.0249191
|View full text |Cite
|
Sign up to set email alerts
|

Dog Owners’ Survey reveals Medical Alert Dogs can alert to multiple conditions and multiple people

Abstract: Medical Alert Dogs (MADs) are a promising support system for a variety of medical conditions. Emerging anecdotal reports suggest that dogs may alert to additional health conditions and different people other than those that they were trained for or initially began alerting. As the use of medical alert dogs increases, it is imperative that such claims are documented empirically. The overall aims of this study were to record the proportion of MAD owners who have a dog that alerts to multiple health conditions or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…We assume that this dog was successful because he had a very highly developed sense of smell, he was quick at learning new targets, and he had already mastered several different odor targets, including early-stage cancers. In fact, research has shown that dogs with more trained targets tend to learn a new one more easily [44,45], and only 2 to 3 exposures are needed for such dogs to learn to respond to a novel target odor [46]. Individual differences between the scent detection dogs, as seen here in our study, have been observed in most studies.…”
Section: Discussionsupporting
confidence: 64%
“…We assume that this dog was successful because he had a very highly developed sense of smell, he was quick at learning new targets, and he had already mastered several different odor targets, including early-stage cancers. In fact, research has shown that dogs with more trained targets tend to learn a new one more easily [44,45], and only 2 to 3 exposures are needed for such dogs to learn to respond to a novel target odor [46]. Individual differences between the scent detection dogs, as seen here in our study, have been observed in most studies.…”
Section: Discussionsupporting
confidence: 64%
“…Reports of dogs' abilities to detect human conditions have historically emerged first as anecdotes, which have later been corroborated by in-vitro laboratory studies (e.g., diabetic glucose fluctuation: [29][30][31] and epileptic seizure: [24,32]). When considering dogs' abilities to detect stress in humans, it has been reported in the media that dogs can sense when the humans around them are experiencing stress (e.g., [33,34]), and a recent study by Reeve et al [35] found that, in a questionnaire to owners of trained Medical Alert Dogs, stress was the most common condition to which dogs were reported to alert. The current study addresses this reported phenomenon using a controlled, in-vitro, bio-detection paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, specially trained pets can provide service to their owners, and even save their lives (e.g. Medical Alert Dogs (MADs) [ 12 ]). People have a strong social and emotional attachment to their pets [ 11 ].…”
Section: Introductionmentioning
confidence: 99%